1971
DOI: 10.1172/jci106502
|View full text |Cite
|
Sign up to set email alerts
|

Association of autoantibodies to different nuclear antigens with clinical patterns of rheumatic disease and responsiveness to therapy

Abstract: A B S T R A C T Using a hemagglutination test which can detect antibodies to (a) native and denatured deoxyribonucleic acid (DNA) and (b) an extractable nuclear antigen (ENA), a comparative study of patterns of autoantibody formation has been done in systemic lupus erythematosus (SLE) and related rheumatic diseases. Antibody to native DNA was present in the serum in 96% of patients with active SLE and disappeared during remissions. Antibody to ENA was found in 86% of those patients with SLE nephritis who respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
6

Year Published

1974
1974
1987
1987

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(103 citation statements)
references
References 34 publications
3
93
1
6
Order By: Relevance
“…Antibodies to extractable nuclear antigens (ENA) were measured by the method of Sharp (17). Rheumatoid factor (RF) was measured by commercial slide latex agglutination test.…”
Section: (16)mentioning
confidence: 99%
“…Antibodies to extractable nuclear antigens (ENA) were measured by the method of Sharp (17). Rheumatoid factor (RF) was measured by commercial slide latex agglutination test.…”
Section: (16)mentioning
confidence: 99%
“…Fractions eluting with a molarity of 0.9 M or less were considered to be nDNA (16,30,31,17), although with KB DNA at least some dDNA was still present (vide infra). The fraction eluting at high pH has been shown to be dDNA (5,17,31). To increase the proportion of this fraction, several chromatographic runs were carried out with DNA which had been heated for 12 minutes in a boiling water bath and cooled immediately.…”
Section: Methylated Albumin-kieselguhr Chromatographymentioning
confidence: 99%
“…These data are comparable to the findings of Fries and Holman who noted no significant difference in cumulative adjusted mortality at either 1, 6, or 30 months after first visit when comparing SLE patients with and without antibody to ENA (10). In contrast are the findings of others (16)(17)(18)(19)(22)(23)(24)(25)(26) who have suggested that antiRNP antibody is associated with a good prognosis; these studies have either excluded SLE patients with antibody to DNA (18) or their study group has been defined by the presence of antiRNP antibody as the "sine qua non" and not by the clinical diagnosis of SLE (17,19,22,23,25,26). Furthermore, a long-term observation of these latter laboratory-defined groups is not available.…”
Section: Discussionmentioning
confidence: 91%